DESIGN OF FPGA BASED ADAPTIVE FILTER BASED ON LMS ALGORITHM FOR ECHO CANCELLATION - Vaibhav S Kadam; Prof. A.B Gaikwad (International Journal of Innovations in Engineering Research and Technology, 2021)
Traditional telephony uses only a single receiver for speech acquisition. If the speaker is standing away from the telephone, the signal will be weak and there will be interference sources from room reverberation. In addition, there is acoustic echo coming from the loudspeaker, which further interferes with the signal of interest. This research investigated the combination of common solutions to these problems. Echo Cancellation is an occurrence in today’s communication systems. The interferences caused by acoustic echo are distracting to the users and reduce the quality of the voice. Echo cancellation removed the echo coming from the loudspeaker. The main component of the system is the adaptive filter.